Oblicz wartość podanego wyrażenia.


A) -12x-(4y²-7)+5x dla x = -2 i y =¼
B)½a +2(-3b +a)-6 dla a = 1ib = -0,5
c)5x-4y(-6x+12)- (-5)y dla x =6iy =-6
d) 7+(-3)(x-2y)-½(-4y+x) dla x= - 0,4 i y = 1,2

..........................................................................
Rozwiąż równanie i sprawdź rozwiązanie równania

-(x-4)²=(3-x)(3+x)

3

Odpowiedzi

2009-12-14T15:28:30+01:00
A) 16
b) -2,5
c) 77
d) - 0,2



x=25
3 2 3
Najlepsza Odpowiedź!
2009-12-14T15:44:13+01:00
A) -12x-(4y²-7)+5x dla x = -2 i y =¼

-12x-4y²+7+5x= -12(-2)-4(¼)²+7+5(-2)=24-4×1/16+7-10=24-4/16+7-10=21-¼=20¾

B)½a +2(-3b +a)-6 dla a = 1ib = -0,5

½a-6b+2a-6=½-6(-0,5)+2-6=½+3+2-6=-1+½=-½

c)5x-4y(-6x+12)- (-5)y dla x =6iy =-6

5x+24xy-48y+5y= 5x+24xy-43y=5×6+24[6(-6)]-43(-6)=30+24(-36)+258=288-864=-576

d) 7+(-3)(x-2y)-½(-4y+x) dla x= - 0,4 i y = 1,2

7-3x+6y+2y-½x=7-3½x+8y=7-3,5(-0,4)+8(1,2)=7+1,4+9,6=18





-(x-4)²=(3-x)(3+x)

-(x²-8x+16)=9+3x-3x-x²
-x²+8x-16=9-x²
8x=16+9-x²+x²
8x=25
x=25/8
x=3⅛

spr; -(25/8-4)²=(3-25/8)(3+25/8)
-(-⅞)²=-⅛(49/8)
-(49/64)=-49/64
-49/64=-49/64
2 3 2
2009-12-14T15:45:20+01:00
A) -12x-(4y²-7)+5x=-12*(-2)-(4*¼²-7)+5*(-2)=-24-(4*⅛-7)+(-10)=-24-(½-7)+(-10)=
-24-(-6½)+(-10)=-24+6½+(-10)=-27½

B)½a +2(-3b +a)-6=½*1+2*(-3*(-0,5)+1)-6=½+2*(1,5+1)-6=½+2*2,5-6=½+5-6=-½

c)5x-4y(-6x+12)-(-5)y=5*6-4*(-6)*(-6*6+12)-(-5)*(-6)=30-(-24)*(-36+12)-30=
30-(-24)*(-24)-30=30-576-30=-576

d) 7+(-3)(x-2y)-½(-4y+x)=7+(-3)*(-0,4-2*1,2)-½*(-4*1,2+(-0,4))=
7+(-3)*(-0,4-4,2)-½*(-4,8+(-0,4))=7+(-3)*(-4,6)-½*(-5,2)=7+13,8+10,4=31,2


-(x-4)²=(3-x)(3+x)
-(x²+(-4))²=(3-x)*(3+x)
-(x²+16)=9-3x /-16
-(x*x)=-5-3x
-x*(-x)=-5-3x /+3x
3x-x*(-x)=-5
3x+x*x=-5
5x=-5 //5
x=1
2 3 2